Relationships Between Working Memory, Theory Of Mind, And Verbal Ability Among Iranian Preschool Children - Farhadian, Mokhtar (2010)

(untitled)
A corelational study was carried out to investigate the relationship between working memory (WM), theory of mind (ToM), and verbal ability (VA) among Iranian preschool children. Stratified random sampling method was utilized to identify respondents for the study. One hundred and sixty-three preschool children were selected as respondents in this study. Ninety eight (62%) children were bilingual and 65 (38%) were monolingual children. Data were collected by using a questionnaire and three standardized instruments which included Automated Working Memory Assessment (AWMA), false beliefs tasks and McCarthy Scales of children‟s ability and a questionnaire. The result revealed that the mean scores of bilingual children in working memory, verbal ability, and theory of mind were significantly higher than those of monolingual children. Pearson Product Moment Correlation statistically significant positive correlation were found between working memory and theory of mind (r = .436, p<.05), working memory and verbal ability (r = .426, p<.05) as well as theory of mind and verbal ability (r = .578, p<.05). The result supported a positive relationship between the working memory as well as verbal ability on children‟s theory of mind. Hierarchical regression analysis showed that controlling for age, verbal ability, and working memory, language status did not explain the variance in children‟s theory of mind. The findings suggest that it would be vital for the teachers in preschool age group and also school age to screen working memory capacity among children and apply the appropriate methods to enhance working memory regardless of the kind of language that the children are speaking with.